Detection of Zoonotic Antibiotic Resistant Salmonella spp. Carrying Virulence Genes in Rural Mus musculus, Golestan Province, North of Iran - Somayeh Namroodi (Shahrekord University of Medical Sciences, 2019)
Background and aims: Salmonella spp. infect cold-blooded and warm-blooded animals and may cause a worldwide zoonotic disease, salmonellosis, in infected animals. Rodents can be Salmonella carriers without any signs of salmonellosis. The frequency of salmonella contamination, the presence of virulence genes (SpvR and SpvB) and antibiotic resistance pattern of isolated Salmonella were studied in rural Mus musculus to reveal the possible role of them in Salmonella dissemination in Golestan province. Methods: A total of 190 wet rectal swabs of M. musculus were obtained from rural areas of Golestan province with different climate conditions. The swabs were cultured and positive samples were serotyped and their antibiotic resistance patterns were studied. The presence of Salmonella and virulence genes was analyzed by SpvR and SpvB genes primers, respectively. Results: Salmonella spp. were detected in 15 (7%) of 190 fecal samples by bacterial culture and PCR. S. enteritidis (n=9) and S. typhimurium (n=6) were identified. The highest and lowest frequencies were detected in humid (13.1%) and arid areas (3.1%), respectively. SpvR and SpvB genes were diagnosed in 10 of 15 (66.6%) isolated Salmonella. The highest resistance of detected Salmonella spp. was observed against streptomycin (53%). All the isolates were sensitive to chloramphenicol, gentamicin and trimethoprim. Conclusion: The Salmonella contamination in sampled house mice indicates that native people should be made aware of the risk of Salmonella infection and possible ways of salmonella transmission through rodents. In addition, the application of appropriate therapeutic approaches to prevent the spread of antibiotic resistant Salmonella is recommended.